Comparison of 1 vs 2 Brain Death Examinations on Time to Death Pronouncement and Organ Donation: A 12-Year Single Center Experience. (9th March 2021) - Varelas, Panayiotis N.; Rehman, Mohammed; Mehta, Chandan; Louchart, Lisa; Schultz, Lonni; Brady, Paul; Kananeh, Mohammed F.; Wijdicks, Eelco F.M.
Abstract : Objective: To fill the evidence gap on the value of a single brain death (SBD) or dual brain death (DBD) examination by providing data on irreversibility of brain function, organ donation consent, and transplantation. Methods: Twelve-year tertiary hospital and organ procurement organization data on brain death (BD) were combined and outcomes, including consent rate for organ donation and organs recovered and transplanted after SBD and DBD, were compared after multiple adjustments for covariates. Results: A total of 266 patients were declared BD, 122 after SBD and 144 after DBD. Time from event to BD declaration was longer by an average of 20.9 hours after DBD ( p = 0.003). Seventy-five (73%) families of patients with SBD and 86 (72%) with DBD consented for organ donation ( p = 0.79). The number of BD examinations was not a predictor for consent. No patient regained brain function during the periods following BD. Patients with SBD were more likely to have at least 1 lung transplanted ( p = 0.031). The number of organs transplanted was associated with the number of examinations (β coefficient [95% confidence interval] −0.5 [−0.97 to −0.02]; p = 0.044), along with age (for 5-year increase, −0.36 [−0.43 to −0.29]; p < 0.001) and PaO2 level (for 10 mm Hg increase, 0.026 [0.008–0.044]; p = 0.005) and decreased as the elapsed time to BD declaration increased ( p = 0.019). Conclusions: A single neurologic examination to determine BD is sufficient in patients with nonanoxic catastrophic brain injuries. A second examination is without additional yield in this group and its delay reduces the number of organs transplanted.